Phylogeography of Atlantic Forest glassfrogs (Vitreorana): when geography, climate dynamics and rivers matter - Paz, A.; Spanos, Z.; Brown, J. L.; Lyra, M. [UNESP]; Haddad, C. [UNESP]; Rodrigues, M.; Carnaval, A. (Nature Publishing Group, 2019)
Recent advances in the field of landscape genetics provide ways to jointly analyze the role of present-day climate and landscape configuration in current biodiversity patterns. Expanding this framework into a phylogeographic study, we incorporate information on historical climatic shifts, tied to descriptions of the local topography and river configuration, to explore the processes that underlie genetic diversity patterns in the Atlantic Forest hotspot. We study two montane, stream-associated species of glassfrogs: Vitreorana eurygnatha and V. uranoscopa. By integrating species distribution modeling with geographic information systems and molecular data, we find that regional patterns of molecular diversity are jointly explained by geographic distance, historical (last 120 ky) climatic stability, and (in one species) river configuration. Mitochondrial DNA genealogies recover significant regional structure in both species, matching previous classifications of the northern and southern forests in the Atlantic Forest, and are consistent with patterns reported in other taxa. Yet, these spatial patterns of genetic diversity are only partially supported by nuclear data. Contrary to data from lowland taxa, historical climate projections suggest that these montane species were able to persist in the southern Atlantic Forest during glacial periods, particularly during the Last Glacial Maximum. These results support generally differential responses to climatic cycling by northern (lowland) and southern (montane) Atlantic Forest species, triggered by the joint impact of regional landscape configuration and climate change.